Synthesis and ionic conductivity of calcium-doped ceria relevant to solid oxide fuel cell applications - Momin, Naeemakhtar; Manjanna, J.; Kobayashi, Satoru; Aruna, S. T.; Kumar, S. Senthil; Nayaka, G. P. (Materials Advances, 2022)
Towards the development of green energy devices, it is necessary to focus on commercial electrolyte materials for intermediate temperature solid oxide fuel cells (IT-SOFCs). Ca-doped ceria (CDC) samples having a composition of Ce(1−x)CaxO2−δ (0.03 ≤ x ≤ 0.1) were synthesized by a facile solid-state route and sintered at a lower temperature (1473 K). X-ray diffraction, Raman, X-ray photoelectron, Fourier-transform infrared, UV–VIS diffuse reflectance, field emission scanning electron microscopy – energy dispersive X-ray with elemental mapping, and electrochemical impedance spectroscopy techniques were used for the characterization of these CDC samples. The 0.10 CDC showed high oxide ion conductivity of 8.01 × 10−3 S cm−1 at 973 K with a lower activation energy of 0.78 eV. The 0.03 CDC, 0.05 CDC, and 0.07 CDC samples exhibited ionic conductivities of 1.66 × 10−4, 4.42 × 10−3, and 5.76 × 10−3 S cm−1 at 973 K with activation energies of 1.65, 1.01, and 0.92 eV, respectively. The present work aims to develop Ca-doped ceria as economically viable electrolytes for IT-SOFCs.